Research into the influence of mechanical losses in the plunger pair on the performance of the hydraulic drive - Viunyk, Olha; В'юник, Ольга Володимирівна; Komar, Artem; Комар, Артем Станіславович; Dyachenko, I. (Запоріжжя: ТДАТУ, 2025)
The work is part of a series of articles devoted to increasing the durability of plunger pairs of axial piston pumps. The structural parameters that affect the mechanical losses of an axial piston hydraulic pump include the wear of parts in the following combinations: "annular heel support - cradle support" (for a hydraulic pump) and "plunger block sleeve". Let us consider the working hypothesis that the wear of the annular support causes mechanical losses that affect the performance of the hydraulic drive. Let us conduct a preliminary analysis of the technical condition of the annular heel support in operating conditions at a qualitative level, and also consider the operating conditions of the plunger pair.
Keywords: hydraulic drive; plunger pair